1973
DOI: 10.1302/0301-620x.55b3.513
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Estimation of Vertebral Rotation in Scoliosis

Abstract: 1. The radiographic appearance of normal thoracic and lumbar vertebrae at 15-degree intervals of rotation is described. Each image can be identified by its characteristic features. 2. The appearance on antero-posterior radiographs of apical vertebrae in scoliosis closely resembles the normal at each phase of rotation, on the basis of which an image-matching method is proposed for estimating rotation in scoliosis. 3. The method gives only approximate values of rotation but has the advantage of being able to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…The search for a precise analysis of vertebral rotation associated with scoliosis is hardly new: various methods have been described by Cobb [5], Nash and Moe [11], Perdriolle [12] or Mehta [13], all of which are based on evaluation of the relative position of posterior vertebral elements. Although Perdriolle's torsiometer became the most widely used in clinical practice, its reproducibility and accuracy are very limited [14].…”
Section: Introductionmentioning
confidence: 99%
“…The search for a precise analysis of vertebral rotation associated with scoliosis is hardly new: various methods have been described by Cobb [5], Nash and Moe [11], Perdriolle [12] or Mehta [13], all of which are based on evaluation of the relative position of posterior vertebral elements. Although Perdriolle's torsiometer became the most widely used in clinical practice, its reproducibility and accuracy are very limited [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors [4, 5,7,8,19,20,24,32] have used a variety of geometrical formulae that take into account the diverse anatomical frames of the vertebrae as projected in coronal radiographs to develop a quantitative measurement of axial rotation, implicitly referred to the global referential system. Indeed, the concept of axial rotation of the scoliotic curve vertebrae requires a single referential system for all the vertebrae.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Grossiord et al [12] and Nash and Moe [21] showed that the position of the pedicle shadow with respect to those of the vertebral body wedges and the posterior arch provided a more sensitive index. They also showed that accurate calibration of the X-ray machine was most important, as the coronal view of the spine provides only a frontal projection of the vertebrae, and hence a qualitative evaluation of the axial rotation.Several authors [4, 5,7,8,19,20,24,32] have used a variety of geometrical formulae that take into account the diverse anatomical frames of the vertebrae as projected in coronal radiographs to develop a quantitative measurement of axial rotation, implicitly referred to the global referential system. Indeed, the concept of axial rotation of the scoliotic curve vertebrae requires a single referential system for all the vertebrae.…”
mentioning
confidence: 99%
“…The Cobb method was found suitable for measuring minor degrees of rotation (Mehta 1973). The methods of measuring rotation from the tip of processus spinosus (Cobb 1948) has been criticized (Nash & Moe 1969) as has the pedicle method of Nash & Moe (Benson et al 1976).…”
mentioning
confidence: 99%